Association between Doppler assessment and secondary cesarean delivery for intrapartum fetal compromise in small-for-gestational-age fetuses - Scholz, Anna; Rónay, Vanessa; Wallwiener, Markus; Fluhr, Herbert; Au, Alexandra von; Spratte, Julia; Wallwiener, Stephanie; Elsässer, Michael (Archives of gynecology and obstetrics, 2024)
PURPOSE: To elucidate the association between arterial and venous Doppler ultrasound parameters and the risk of secondary cesarean delivery for intrapartum fetal compromise (IFC) and neonatal acidosis in small-for-gestational-age (SGA) fetuses. METHODS: This single-center, prospective, blinded, cohort study included singleton pregnancies with an estimated fetal weight (EFW) < 10th centile above 36 gestational weeks. Upon study inclusion, all women underwent Doppler ultrasound, including umbilical artery (UA) pulsatility index (PI), middle cerebral artery (MCA) PI, fetal aortic isthmus (AoI) PI, umbilical vein blood flow (UVBF), and modified myocardial performance index (mod-MPI). Primary outcome was defined as secondary cesarean section due to IFC. RESULTS: In total, 87 SGA pregnancies were included, 16% of which required a cesarean section for IFC. Those fetuses revealed lower UVBF corrected for abdominal circumference (AC) (5.2 (4.5-6.3) vs 7.2 (5.5-8.3), p = 0.001). There was no difference when comparing AoI PI, UA PI, ACM PI, or mod-MPI. No association was found for neonatal acidosis. After multivariate logistic regression, UVBF/AC remained independently associated with cesarean section due to IFC (aOR 0.61 [0.37; 0.91], p = 0.03) and yielded an area under the curve (AUC) of 0.78 (95% CI, 0.67-0.89). A cut-off value set at the 50th centile of UVBF/AC reached a sensitivity of 86% and specificity of 58% for the occurrence of cesarean section due to IFC (OR 8.1; 95% CI, 1.7-37.8, p = 0.003). CONCLUSION: Low levels of umbilical vein blood flow (UVBF/AC) were associated with an increased risk among SGA fetuses to be delivered by cesarean section for IFC.
Gesehen am 03.09.2024